2015
DOI: 10.1186/s40064-015-1011-x
|View full text |Cite
|
Sign up to set email alerts
|

GHM method for obtaining rationalsolutions of nonlinear differential equations

Abstract: In this paper, we propose the application of the general homotopy method (GHM) to obtain rational solutions of nonlinear differential equations. It delivers a high precision representation of the nonlinear differential equation using a few linear algebraic terms. In order to assess the benefits of this proposal, three nonlinear problems are solved and compared against other semi-analytic methods or numerical methods. The obtained results show that GHM is a powerful tool, capable to generate highly accurate rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It exploits the well-known concept of multiparameter homotopy continuation methods to the homotopy perturbation techniques. (v) e generalized homotopy method [16,17] is a powerful generalization of the homotopy perturbation method [18][19][20]. It consists on replacing the traditional power series (v 0 + v 1 p + v 2 p 2 + • • •) of the homotopy parameter p by a power series of a trial function with respect to p. is paradigm change converts HPM into an especial case of GHM.…”
Section: Introductionmentioning
confidence: 99%
“…It exploits the well-known concept of multiparameter homotopy continuation methods to the homotopy perturbation techniques. (v) e generalized homotopy method [16,17] is a powerful generalization of the homotopy perturbation method [18][19][20]. It consists on replacing the traditional power series (v 0 + v 1 p + v 2 p 2 + • • •) of the homotopy parameter p by a power series of a trial function with respect to p. is paradigm change converts HPM into an especial case of GHM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obtained numerical solution may not represent the desired result [3,4]. Hence, a line of research is focused to obtain solutions in the form of analytical approximations like: enhanced power series method [5], power series extender method [6,7], modified Taylor series method [8], direct Padé method [9,10], rational homotopy perturbation method [11], generalized homotopy method [12,13], homotopy analysis method [2,14], homotopy perturbation method [15,16,17], among others. On one hand, all above mentioned methods may provide approximate solutions in terms of polynomials; nevertheless, users require specialized knowledge of mathematics to apply such methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors applied HPM to solve linear and nonlinear partial differential equations of fractional order (Momani and Odibat 2007a , b ), Volterra integral equations (Grover and Tomer 2011 ), singularly perturbed Volterra integral equations (Alnasr and Momani 2008 ) and n-th order fuzzy linear differential equations (Tapaswini and Chakraverty 2013 ). The reader is also referred to two recent papers where the authors (Filobello-Nino et al 2014a ; Vazquez-Leal and Sarmiento-Reyes 2015 ) make use of HPM in their application oriented works. In the very recent studies, it has been found that homotopy perturbation method was also used to solve fractional fisher’s equation (Hamdi Cherif et al 2016 ) and a system of nonlinear chemistry problems (Ramesh Rao 2016 ).…”
Section: Introductionmentioning
confidence: 99%